Penerapan Teknologi Digital Untuk Tranformasi Pariwisata Berbasis Komunitas di Desa Sugihen - Yogi Putra; Beby Asdilvira (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2025)
To improve the competitiveness and well-being of local communities, the growth of community-based village tourism requires the assistance of digital technology. Although Sugihen Village has significant potential for natural and cultural tourism, the use of digital technology in tourism administration and promotion is still minimal. The objective of this community service project is to utilize digital technology to transform community-based tourism in Sugihen Village. The approach used was Participatory Action Research (PAR), which included the stages of needs analysis, digital literacy training and capacity building, implementation of digital tourism technology, mentoring, monitoring, and evaluation. The results of the community service included increased community digital literacy, a stronger position of the Pokdarwis institution in tourism management, and a shift in community perspectives on the use of digital technology as a consequence of the community service activities. In addition to being a marketing tool, digital technology also empowers the community in independent and sustainable tourism management. This activity concluded that the independence of the Sugihen Village community can be strengthened and community-based tourism can be transformed through the use of digital technology accompanied by a participatory approach.